The Ever-Expanding Immunomodulatory Role of Calreticulin in Cancer Immunity - de Bruyn, Marco; Wiersma, Valerie R.; Helfrich, Wijnand; Eggleton, Paul; Bremer, Edwin (Frontiers in Oncology, 2015)
Calreticulin is a pleiotropic molecule that normally resides in the lumen of the endoplasmatic reticulum (ER). Here it has various functions, ranging from regulation of calcium homeostasis to ensuring proper protein folding. More recently, calreticulin gained especial interest for its extracellular functions, where it has direct immunomodulatory activity. In this respect, calreticulin activates dendritic cells (DCs) and macrophages. In addition, certain anti-cancer therapies induce the translocation of calreticulin from the ER to the cell surface of dying cancer cells, where calreticulin dictates the immunogenicity of these cells. Interestingly, treatment with Tumor Necrosis Factor (TNF)-Related Apoptosis Inducing Ligand (TRAIL) also induces membrane calreticulin exposure on cancer cells. As shown here, calreticulin directly interacts with TRAIL and its receptor (TRAILR)-signaling complex, as well as with other TNF family members. Of note, TRAIL is a well known immunomodulatory molecule, and is expressed on the surface of natural killer T-cells (NK T-cells). Therefore, calreticulin may have an as yet unrecognized wide(r) impact on immunity, with the TNF ligand family modulating virtually all aspects of the immune response.